Edupreneur: Developing Boardgame As a product of University Entrepreneurial Activities - Seta Ariawuri Wicaksana; Wustari Larasati Mangundjaya (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This paper will discuss the effectiveness of board games as an educational tool in people's development and the possibility of boardgame as a university product. Developing a board game as an alternative to entrepreneurship products was explored as a stimulating learning program, especially for the adult learning program. People need to gain more competencies to be accelerating with the current condition and compete in this era, as competencies are essential, so people must acquire and learn new competencies. Meanwhile, learning is not a one-way round; it is a complex process that needs to emerge within themself. Board games are instruments that can help people learn new competencies and enhance people capacity, with fun and enjoyable way. Design/methodology/approach: This study uses quantitative research with 70 respondents consist of 60 respondents as the participant of boardgame and 10 lecturers. Findings: Board games could be a learning method that is fun, challenging, and engaging for participants. Board games are great tools to be used as they follow the andragogy assumptions, hence positively impacting learning. This study aims to give scientific studies on the use of board games in human development settings. As well as the opportunity of the University to develop the edupreneurship within their university. Research limitations/implications: First, this study only conducted at the participants from one holding company that participates in the training program. Further study with larger participants and from various companies is recommended. Second, this study only uses simple descriptive analysis from the participant's evaluation and lecturer’s opinion, different types of data collection tools might be used in the further study. Practical implications: The study also showed that universities should take part in developing entrepreneurship activities by supporting them. The study also revealed that boardgame could become one of the products from the University, especially from the Faculty of Psychology. Originality/value: Exploring the board games as a learning method that is fun, challenging, and engaging for participants., as well as the possibility of earning income for the lecturers, students and lecturers. Paper type: Research Paper